Entraves na finalização do percurso formativo no curso Técnico Subsequente em Serviços Públicos do IFRR/CBVZO - Oliveira, Hudson do Vale de (2024)
The study aims to analyze the main challenges faced by students of the Technical Course in Public Services Subsequent to High School at IFRR/CBVZO and the possible alternatives and pedagogical strategies that can be implemented to enable the completion of the course. The specific objectives are: a) to understand the challenges faced and the students' perception regarding possible solutions for completing the course; b) to analyze how students who dropped out perceive such challenges from the perspective of overcoming them, with a focus on its completion; c) to map, in light of the perception of students who dropped out and others involved in the phenomenon, in what way(s) the completion of the course could be made possible; and d) to present as an educational product a manual with alternatives for the “rescue” of students who dropped out. The study, aligned with the research line “Organization and Memories of Pedagogical Spaces in Professional and Technological Education” and centered within the macroproject “Organization of Pedagogical Spaces of EPT” by ProfEPT, presents a qualitative approach, of an applied, exploratory and descriptive nature, using bibliographical and documentary research and case study as procedures. It was carried out at IFRR/CBVZO, specifically with students who dropped out of classes of the Technical Course in Public Services subsequent to high school, also considering the teachers and administrative technicians who worked with the course, as well as managers. In data collection, the following techniques were considered: a) application of forms to the students; b) conducting interviews with the teachers who worked in the course, as well as with the technical team that supported its implementation and, also, with the managers; and, c) the analysis of the guiding documents for the creation of the technical courses offered by IFRR/CBVZO, focusing on aspects related to the research in question. The research was submitted to the Research Ethics Committee (CEP), following the procedures required for conducting research with human beings. The information collected was analyzed qualitatively, using content analysis (Bardin, 2016). As an outcome of the research, with regard to the elaboration of the educational product, a Manual of Alternatives for Assistance to Students Who Drop Out Of the Technical Course Following High School in Public Services of IFRR/Boa Vista West Zone Campus was produced, therefore considering the different perceptions and suggestions of the actors involved in the study. We found that, in relation to not completing the course, the greatest difficulty presented by the students who dropped out was the demands related to the curricular internship. When we analyzed this result, we identified that the biggest problem for students who dropped out was related to writing the report, and some even indicated that they felt blocked when faced with the need to write down their reports about their internship